2004
DOI: 10.1159/000077718
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Chemoattractant Protein-1 Serum Levels in Patients with Breast Cancer

Abstract: The chemokine monocyte chemoattractant protein (MCP)-1 is thought to be involved in breast carcinogenesis. We evaluated MCP-1 serum levels in patients with breast cancer (n = 135), ductal carcinoma in situ (DCIS) I–III (n = 30), benign breast lesions (n = 143) and in healthy women (n = 27). We determined the value of MCP-1 serum levels as a differentiation marker between malignant, preinvasive and benign breast diseases and as a predictive marker for the biological phenotype of breast carcinoma. Median (range)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
72
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(78 citation statements)
references
References 15 publications
4
72
1
1
Order By: Relevance
“…It requires binding of tumor cells to specific adhesion molecules on the surface of endothelial cells. Chemokines, such as monocyte chemoattractant protein-1 (MCP-1) (Lebrecht et al, 2004;Kuroda et al, 2005) and several adhesion molecules, including vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) (Silva et al, 2006;Kobayashi et al, 2007), are involved in this process. It is striking to notice that MCP-1, VCAM-1 and ICAM-1 are classical inflammatory mediators which mediate transendothelial migration of leukocytes (Desideri and Ferri, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It requires binding of tumor cells to specific adhesion molecules on the surface of endothelial cells. Chemokines, such as monocyte chemoattractant protein-1 (MCP-1) (Lebrecht et al, 2004;Kuroda et al, 2005) and several adhesion molecules, including vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) (Silva et al, 2006;Kobayashi et al, 2007), are involved in this process. It is striking to notice that MCP-1, VCAM-1 and ICAM-1 are classical inflammatory mediators which mediate transendothelial migration of leukocytes (Desideri and Ferri, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported a trend toward higher levels of circulating MCP-1 in breast cancer patients compared to age-matched controls [18], with no significant correlation to commonly used prognostic indicators identified. A consensus has yet to be reached as to whether circulating MCP-1 is a positive or negative prognostic indicator in breast cancer patients [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Over 50% of breast cancer tumor samples had intense staining of CCL2 in tumor cells (22). Prognostic analysis further revealed that high expression of CCL2 was correlated with advanced tumor stage, lymph node metastasis (23), and early relapse (24). CCL2 up-regulation in breast tumors was also associated with the infiltration of tissue-associated macrophages (TAMs) 3 and with increased microvessel density (22,24).…”
mentioning
confidence: 99%